The Effect of SatÄ±sfactÄ±on MedÄ±atÄ±on on the MotÄ±vatÄ±on RelatÄ±onshÄ±p CÄ±tÄ±zenshÄ±p BehavÄ±or Work and OrganÄ±zatÄ±onal - Landra, Nengah; Budiyasa, I Gede Putu Eka; Widyawati, Sapta Rini (Department of Management, Faculty of Economics and Business, Brawijaya University, 2022)
The purpose of this study was to examine the mediating effect of job satisfaction on the relationship between work motivation and organizational citizenship behavior (OCB). Using as many as 106 employees working in several occupations in one of the largest city in Indonesia as respondents and using a path analysis model, the results showed that work motivation had a positive and significant relationship with job satisfaction and OCB, and also found a positive and significant relationship between job satisfaction and OCB. In general, job satisfaction has been shown to mediate the relationship, but the specifics differ, which is caused by the different characteristics among employees. The mediating effect was evident in male employees, older employees and employees with high tenure while female employees, younger employees (< 5 years), the mediating effect was not proven. As for the characteristics of education, it cannot be concluded with certainty, because the explanatory variance is very low.